2021
DOI: 10.1515/cclm-2021-0644
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative profiling of inflammatory and pro-resolving lipid mediators in human adolescents and mouse plasma using UHPLC-MS/MS

Abstract: Objectives Lipid mediators are bioactive lipids which help regulate inflammation. We aimed to develop an ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method to quantify 58 pro-inflammatory and pro-resolving lipid mediators in plasma, determine preliminary reference ranges for adolescents, and investigate how total parenteral nutrition (TPN) containing omega-3 polyunsaturated fatty acid (n-3 PUFA) or n-6 PUFA based lipid emulsions influence lipid mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…It is appropriate to emphasize that these early fundamental studies are vital to understanding the pathogenesis of COVID-19 infections and the potential role of lipid mediators that could give useful new directions for treatments of COVID-19, long COVID and in lasting immunity. These new findings ( Table 1 ) and many other human studies for SPMs from international experts [ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] ] would not have been possible without the i) complete stereochemical assignments of each of the potent bioactive SPMs produced by human and mouse leukocytes, ii) their biosynthesis from n-3 essential fatty acids (EPA and DHA) and iii) total organic synthesis with rigorous matching studies with endogenous SPMs along with our dedicated and talented organic chemistry collaborators summarized herein. In this relatively new SPM field, the Serhan lab has collaborated for many years with Professor Nicos Petasis and colleagues as part of the total synthesis core of our NIH-supported Program Project grant P01GM095467, Professor Trond Hansen and team in Oslo, Norway [ 56 ], Professor Bernd Spur and Anna Rodriguez [ [57] , [58] , [59] ], and the organic synthesis group at Cayman Chemical; for examples, see the custom synthesis of benzo-RvD1 analog mimetic [ 60 ] and the new RvE4 [ 61 ].…”
Section: Spms In Covid-19 Infections and Other Human Studiessupporting
confidence: 67%
See 3 more Smart Citations
“…It is appropriate to emphasize that these early fundamental studies are vital to understanding the pathogenesis of COVID-19 infections and the potential role of lipid mediators that could give useful new directions for treatments of COVID-19, long COVID and in lasting immunity. These new findings ( Table 1 ) and many other human studies for SPMs from international experts [ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] ] would not have been possible without the i) complete stereochemical assignments of each of the potent bioactive SPMs produced by human and mouse leukocytes, ii) their biosynthesis from n-3 essential fatty acids (EPA and DHA) and iii) total organic synthesis with rigorous matching studies with endogenous SPMs along with our dedicated and talented organic chemistry collaborators summarized herein. In this relatively new SPM field, the Serhan lab has collaborated for many years with Professor Nicos Petasis and colleagues as part of the total synthesis core of our NIH-supported Program Project grant P01GM095467, Professor Trond Hansen and team in Oslo, Norway [ 56 ], Professor Bernd Spur and Anna Rodriguez [ [57] , [58] , [59] ], and the organic synthesis group at Cayman Chemical; for examples, see the custom synthesis of benzo-RvD1 analog mimetic [ 60 ] and the new RvE4 [ 61 ].…”
Section: Spms In Covid-19 Infections and Other Human Studiessupporting
confidence: 67%
“…Importantly, the many other elegant human studies on SPMs would not have been possible without reliance on the complete stereochemically defined synthetic SPMs and their internal standards for LC-MS-MS-based analyses with adult tissues [ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] ] and adolescent human peripheral blood samples [ 38 ] as well as their scale-up for commercial availability [ 62 ]. A recent clinical trial reported that local topical treatment of gingival inflammation with a proresolving lipoxin/resolvin stable analog is safe and effective as well as activated endogenous production of SPMs present in peripheral blood [ 63 ].…”
Section: Spms In Covid-19 Infections and Other Human Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike other methods they used a base modified LC solvent, thus enhancing the ionization process in negative ESI mode. This alternative analytical technique is most probably the reason why their method is 100-fold more sensitive ( Hartling et al, 2021 ).…”
Section: Quantitative Analysis and Spm Levels In Humansmentioning
confidence: 99%